Annual Plant Reviews Online 2020
DOI: 10.1002/9781119312994.apr0726
|View full text |Cite
|
Sign up to set email alerts
|

Functional Strategies and Life Histories of Grasses Underlying Yield and Resilience

Abstract: The family of Poaceae (grasses) includes many economically important crops. While grass grain crops (cereals) are typically annual, bioenergy and forage crops can have annual or perennial life histories. Annuals and perennials differ in important life history traits, such as the regulation of flowering and senescence, which determine to what extent resources are allocated to the grain, vegetative growth, or storage. These differences are also reflected in physiological characteristics; in particular, leaf trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Recently, Yu et al (2022) used the StrateFy tool for alpine Tibetan grasslands, demonstrating that stress tolerator strategies dominated. Using the same method, intrageneric and intraspecific variation was found for the grass genus Brachypodium , showing variation along the S and R axes in perennial Brachypodium species, while the annual model species B. distachyon was classified to have a less competitive strategy ( Crowley and Wingler 2020 ). Intraspecific variation in functional strategies was also described for perennial ryegrass ( Lolium perenne ), demonstrating a trade-off between growth and dehydration survival ( Keep et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yu et al (2022) used the StrateFy tool for alpine Tibetan grasslands, demonstrating that stress tolerator strategies dominated. Using the same method, intrageneric and intraspecific variation was found for the grass genus Brachypodium , showing variation along the S and R axes in perennial Brachypodium species, while the annual model species B. distachyon was classified to have a less competitive strategy ( Crowley and Wingler 2020 ). Intraspecific variation in functional strategies was also described for perennial ryegrass ( Lolium perenne ), demonstrating a trade-off between growth and dehydration survival ( Keep et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intraspecific variation in functional strategies was also described for perennial ryegrass ( Lolium perenne ), demonstrating a trade-off between growth and dehydration survival ( Keep et al 2021 ). Such variation is reflected in CSR classification, which showed that perennial ryegrass has a mainly ruderal strategy, but with variation along the S- and R-axes ( Crowley and Wingler 2020 ).…”
Section: Introductionmentioning
confidence: 99%